Simulation of Mathematical Model of Network Interference on Global System for Mobile Communication - Aderinto, Yidiat O.; Musa , Yusuf (Tanzania Journal of Science, 2023)
Network interference is the incorporation of undesirable signals to desirable ones in an interconnected system. In this paper, the simulation of mathematical model of network interference with respect to global system of mobile communication is presented. The model was formulated and analyzed mathematically. Numerical simulation was carried out using real life data from Communication Towers Nigeria Limited, Northwest regional office Kaduna, Nigeria. The results obtained were very close to that of laboratory investigation. Keywords: Mathematical Model, Network, Interference, Congestion, Mobile communication, Stability